The understandings of barakah from the Qur’an: a study of five of its categories - El-Awaisi, Khalid (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Arabic term "Barakah" is used to this day amongst Muslims in their different languages as a very popular supplication for prosperity. The term was mentioned in the Qur’an on numerous occasions in different contexts, some referring to a physical dimension while others refer to a spiritual one. This paper sets out to examine the Qur’anic concept of Barakah by examining the meaning of Barakah within the Qur’anic context. It will explore the different usages of Barakah in the Qur’an and the understandings that could be deduced from them through investigating Quranic verses and their exegesis from both classical and modern works of Tafsir. The paper concludes that Barakah in the Quran comes in numerous context and carries many important meanings turning something that seems ordinary into something extraordinary with incredible characteristics. Although Barakah maybe subtle and invisible only some aspects are understood which have been named and identified in the Quranic and Prophetic texts.